The Magoi and Daimones in Column vi of the Derveni Papyrus - Ahmadi, Amir (Numen, 2014)
Since its discovery in 1962, the Derveni papyrus has been the object of keen scholarly interest. The text consists in the main of an allegorical interpretation of an Orphic poem. The cosmology of the author comes from pre-Socratic physics, in terms of which he casts the Orphic theogony, presumably in order to reveals its truth. The extant text also contains a few badly damaged columns about the afterlife and, seemingly, some rites that facilitate the passage of the soul to the beyond. Here, we find a reference to a rite performed by the magoi that the author compares with the mysteries. Scholars have generally taken the view that these magoi are either Greek religious experts or charlatans. Because of this, scant attention has been paid to the question of possible Iranian background of the rite and the daimones. In this article, I will address this question in reference to relevant Iranian evidence. My conclusion is that, in column 6 of the papyrus, we indeed have an authentic description of a rite rooted in Iranian religious lore, and that behind the magoi’s daimones may well be the ancient Iranian gods, the daēvas.